Juridical Review of Using Criminal Law in Settlement of Land Disputes Based On Government Regulation Number 24 Year 1997 on Land Registration - Jushendri Jushendri (Journal of World Conference (JWC), 2020)
The National Land Agency (abbreviated as BPN) is a non-ministerial government agency in Indonesia that has the task of implementing national, regional and sectoral land governance so as to facilitate BPN linkages that require an important role in its resolution. This study uses normative juridical data so that the data used is sourced from legal literature and literature. The conclusion of this research is that in the realm of law it can be said that disputes are a problem between two or more people where both are concerned about one another in certain objects. This happens because of a misunderstanding or difference of opinion or perception between the two which then causes legal consequences for both. In criminal law, land disputes are usually included in land grabbing as regulated in Article 385 of the Criminal Code which explains that "someone who unlawfully sells, exchanges land that is not his property to another party and gains profits from his actions, is liable to a maximum of four years in prison.